2013
DOI: 10.2337/dc12-2391
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin Lowers Postprandial Glucose and Insulin by Delaying Intestinal Glucose Absorption in Addition to Increasing Urinary Glucose Excretion

Abstract: OBJECTIVECanagliflozin, a sodium glucose cotransporter (SGLT) 2 inhibitor, is also a low-potency SGLT1 inhibitor. This study tested the hypothesis that intestinal canagliflozin levels postdose are sufficiently high to transiently inhibit intestinal SGLT1, thereby delaying intestinal glucose absorption.RESEARCH DESIGN AND METHODSThis two-period, crossover study evaluated effects of canagliflozin on intestinal glucose absorption in 20 healthy subjects using a dual-tracer method. Placebo or canagliflozin 300 mg w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
213
2
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(236 citation statements)
references
References 26 publications
14
213
2
7
Order By: Relevance
“…Inhibition of gut SGLT1 reduces absorption of glucose there, and it has been suggested that canagliflozin may have a dual action. This was reported first in healthy volunteers 53 but has since been reported in a study of people with type 2 diabetes. 54 Because these drugs act through an insulin-independent mechanism, they can be effective when other drugs that depend entirely (sulfonylureas and meglitinides) or in part (gliptins and GLP-1 analogues) on stimulating insulin release have lost effectiveness.…”
Section: Sodium-glucose Co-transporter 2 Inhibitorsmentioning
confidence: 93%
“…Inhibition of gut SGLT1 reduces absorption of glucose there, and it has been suggested that canagliflozin may have a dual action. This was reported first in healthy volunteers 53 but has since been reported in a study of people with type 2 diabetes. 54 Because these drugs act through an insulin-independent mechanism, they can be effective when other drugs that depend entirely (sulfonylureas and meglitinides) or in part (gliptins and GLP-1 analogues) on stimulating insulin release have lost effectiveness.…”
Section: Sodium-glucose Co-transporter 2 Inhibitorsmentioning
confidence: 93%
“…The effects of SGLT2 inhibitors on renal glucose kinetics were assessed using controlled glucose infusion experiments in rats (13) and humans (14,15). These experiments showed that SGLT2 inhibition leads to a reduction in T M G and RT G while maintaining a threshold-like relationship between PG and the UGE rate (Fig.…”
Section: Role Of Sglt2 and Sglt1 In Renal Glucose Reabsorptionmentioning
confidence: 99%
“…Approximately 180g of glucose is filtered through the renal system daily with almost 90% reabsorbed in the proximal tubule by the glucose transporter protein, SGLT-2 [7]. Canagliflozin is a selective SGLT-2 inhibitor which increases urinary excretion of glucose but is associated with an increased rate of GU infections [8].…”
Section: Discussionmentioning
confidence: 99%